Young people with prior health service contacts have increased risk of repeated alcohol-related harm hospitalisations - Sims, S.A.; Pereira, Gavin; Preen, D.; Fatovich, D.; O'Donnell, M. (WILEY, 2022)
Introduction: After a first alcohol-related hospitalisation in youth, subsequent hospitalisations may demonstrate an increased risk of further alcohol-related hospitalisations, but there is no existing data on this. Methods: A retrospective longitudinal study between July 1992 and June 2017 using linked hospital administrative data identified 23 464 Western Australian young people [9009 (38.4%) females and 14 455 (61.6%) males], aged 12–24 years hospitalised for at least one alcohol-related harm (ARH) episode of care. Cox regression was used to estimate hazard ratios (HR) between risk factors and repeated alcohol-related hospitalisation after the first discharge for ARH. Results: Of those admitted for an alcohol-related hospitalisation (n = 23 464), 21% (n = 4996) were readmitted for ARH. This high-risk sub-group comprised 46% (n = 16 017) of the total alcohol-related admissions (n = 34 485). After the first discharge for ARH, 16% (804) of people who experienced an alcohol-related readmission were readmitted within 1 month, and 51.8% (2589) were readmitted within 12 months. At increased risk of readmission were Aboriginal people and those with prior health service contacts occurring before their first alcohol-related hospitalisation, including illicit drug hospitalisations, mental health contacts and, in a sub-analysis, emergency department presentations. Discussion and Conclusions: The probability of a repeated ARH hospitalisation was highest in the first month after initial discharge. There is a high-risk sub-group of young people more likely to have a repeat ARH hospitalisation. This represents an opportunity to provide interventions to those most at risk of repeated ARH.